Case report of combined photodynamic therapy and distant gamma-ray therapy of metastases of skin melanoma - V. L. Filinov (Biomedical Photonics)
Results of follow-up of patient with melanoma metastases to inguinal lymph nodes (two tumor foci) are represented. The patient underwent a course of combined photodynamic therapy and distant gamma-ray therapy. Single intravenous injection of fotosens as photosensitizer at dose of 0.3 mg/kg was administered to the patient. Distant gamma-ray therapy was performed daily during 12 days (single dose of 3 Gy, total dose of 36 Gy), beginning in a day after injection of photosensitizer. Two hours after gamma-ray therapy session contact photodynamic therapy on both metastatic tumors was performed. There were 7 sessions of photodynamic therapy in all, total light dose on each tumor accounted for 1800 J. Three weeks after combined modality treatment the second step of radiotherapy on inguinal region including 12 daily irradiation sessions (single dose of 3 Gy, total dose of 36 Gy) was performed. One year after treatment the patient had complete tumor resorption proved in 6 months. There were no additional treatment during this period in this patient. The patient is still under follow-up.